Editorial: Emerging topics in coastal and transitional ecosystems: science, literacy, and innovation - Duarte, Bernardo (2022)
Marine coastal and transitional ecosystems are facing increasing impacts, and often reflect the most immediate effects of environmental change, habitat destruction, and biodiversity loss. With over half of the population currently living in coastal areas, these areas are of interest for multiple uses and resources, as well as subjected to multiple stressors and associated impacts derived from local and upstream anthropogenic activities. The challenges coastal and transitional ecosystems now face is not new and have far-reaching implications for the ocean (Borja et al.). Nevertheless, significant knowledge gaps on their functioning and structure still exist and new solutions or approaches to this old problem are still needed, from blue biotechnological innovations to improved ocean literacy (Borja et al.). This Research Topic aimed to contribute to the sustainability of coastal and transitional environments, providing a broad overview of ecosystem resources and functioning, assessment and monitoring tools, restoration, biotechnology, and ocean literacy. A growing human population has also increased the reliance on the sea for food and feed resources. Despite soaring demand, the management of seafood resources is still hampered by key knowledge gaps on many life-history traits of target species as well as on ecosystem’s functioning (Golden et al., 2021). From tropical regions, where mangroves function as nursery habitats for various crustaceans and fish species, contributing to maintaining adjacent marine stocks, a poorly studied system on Príncipe Island, Gulf of Guinea, evidenced the importance of seasonality and mangrove zone on fish assemblages (Cravo et al.). In the deep sea, a particular challenge to commercial exploitation of fish species is how changing environmental conditions affect these organisms, which are generally characterized by high longevity, late reproduction, and low fecundity.